PENGARUH MODEL PEMBELAJARAN RADEC BERBANTUAN MULTIMEDIA INTERAKTIF TERHADAP LITERASI LINGKUNGAN SISWA PADA PEMBELAJARAN IPAS. - Pujiawati, Tita; Dadang Hafid; Poppy Anggraeni (LPPM UNSAP & Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aims to determine the effect of the Read Answer Discuss Explain and Create (RADEC) learning model assisted by interactive multimedia on students' environmental literacy in science learning. The method used in this research is an experimental method with a pre-experimental type. The design used is One-Group Pretest-Posttest Design. The population of this study was 25 grade IV students at SDN Cilaku, Cimanggung District, Sumedang Regency. The sampling technique uses a total sampling technique. The instruments used are observation sheets and test sheets. The data collection technique in this research is an observation sheet used to observe student and teacher activities in learning and a test sheet used to measure students' environmental literacy. Data analysis techniques use validity tests, reliability tests, item difficulty level tests, data normality tests, and t tests. Data analysis in this research used Microsoft Excel 2021. The results of research using the t test, students' environmental literacy showed that t_count = 7.509 and t_table = 1.71. So, t_count > t_table then H_0 is rejected and H_1 is accepted. So it can be concluded that there is an influence of using the Read Answer Discuss Explain and Create (RADEC) learning model assisted by interactive multimedia on students' environmental literacy in science and science learning in Class IV SDN Cilaku.